Umbral Interpolation: A Survey - Francesco Aldo Costabile; Maria Italia Gualtieri; Anna Napoli (Mathematics)
A survey on recent umbral polynomial interpolation is presented. Some new results are given, following a matrix-determinant approach. Some theoretical and numerical examples are provided.